Analisis Pengaruh Ukuran Perusahaan, Tingkat Pertumbuhan Perusahaan, dan Risiko Bisnis Terhadap Struktur Modal Perusahaan Food and Beverage Yang Terdaftar Di Bursa Efek Indonesia (Studi Kasus Pada Tahun 2007-2015) - Hapsari, Dinar Intan; , Sri Murwanti,SE.,MM (2015)
This study aims to determine the effect of firm size, company growth rate, and business risk on capital structure. The data used is secondary data. To obtain data from these variables, taken from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange from 2007 to 2015. Sampling technique using purposive sampling technique from 19 food and beverage companies listed in Indonesia Stock Exchange obtained 14 companies that match the criteria. As for the method of analysis and hypothesis test using multiple linear regression. From the results of this study the size of the company and business risks have a significant influence on capital structure, while the growth rate companies have no significant effect on capital structure. In F test indicate that jointly variable of company size, company growth rate and business risk have significant effect to capital structure. Keywords: Business Risk, Capital Structure, Company Growth Rate, Company Size